Thematic domain analysis for ocean modeling. (April 2022) - Jung, Reiner; Gundlach, Sven; Hasselbring, Wilhelm
Abstract: Ocean science is a discipline that employs ocean models as an essential research asset. Such scientific modeling provides mathematical abstractions of real-world systems, e.g., the oceans. These models are then coded as implementations of the mathematical abstractions. The developed software systems are called models of the real-world system. To advance the state in engineering such ocean models, we intend to better understand how ocean models are developed and maintained in ocean science. In this paper, we present the results of semi-structured interviews and the Thematic Analysis (TA) of the interview results to analyze the domain of ocean modeling. Thereby, we identified developer requirements and impediments to model development and evolution, and related themes. This analysis can help to understand where methods from software engineering should be introduced and which challenges need to be addressed. We suggest that other researchers extend and repeat our TA with model developers and research software engineers working in related domains to further advance our knowledge and skills in scientific modeling. Highlights: Thematic analysis of interview results to better understand scientific software development practices in ocean science. The needs of the developers and obstacles that are a hindrance for model development and evolution have been identified. Selected areas as particularly pressing and also promising for improving ocean system modeling are indicated.